2021
DOI: 10.1038/s42003-021-02861-0
|View full text |Cite
|
Sign up to set email alerts
|

Observational and genetic evidence highlight the association of human sleep behaviors with the incidence of fracture

Abstract: We combined conventional evidence from longitudinal data in UK Biobank and genetic evidence from Mendelian randomization (MR) approach to infer the causality between sleep behaviors and fracture risk. We found that participants with insomnia showed 6.4% higher risk of fracture (hazard ratio [HR] = 1.064, 95% CI = 1.038–1.090, P = 7.84 × 10−7), falls and bone mineral density (BMD) mediated 24.6% and 10.6% of the intermediary effect; the MR analyses provided the consistent evidence. A U-shape relationship was ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
3
17
1
Order By: Relevance
“…Our study also found that waking up frequently during the night increased the risk of falls in elderly people with visual impairment. Previous studies have reported that subjective poor sleep quality ( 17 ), napping ( 18 ), short sleep duration ( 19 , 20 ), long sleep duration ( 20 ), and insomnia ( 21 ) were associated with an increased risk of falls and fractures ( 22 , 23 ). Waking up frequently at night is one kind of sleep disorders that reduce sleep quality ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that waking up frequently during the night increased the risk of falls in elderly people with visual impairment. Previous studies have reported that subjective poor sleep quality ( 17 ), napping ( 18 ), short sleep duration ( 19 , 20 ), long sleep duration ( 20 ), and insomnia ( 21 ) were associated with an increased risk of falls and fractures ( 22 , 23 ). Waking up frequently at night is one kind of sleep disorders that reduce sleep quality ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mediation analysis suggested that BMD had larger intermediary effect than falls between BMI and fracture risk. Interestingly, our previous study to investigate the relationship between insomnia and fracture suggested a larger intermediary effect by falls than BMD ( Qian et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there were some explanations for the controversial findings, leveraging genetic data to infer the causal relationship between exposure and outcome could be additional evidences for association ( Xia et al., 2020 ; Qian et al., 2021 ). Therefore, in the present study, we firstly conducted a prospective observational study to investigate the relationship between general obesity index (BMI), abdominal obesity indices (waist circumference adjusted for BMI [WCadjBMI], and hip circumference adjusted for BMI [HCadjBMI]) and fracture risk using the UK Biobank dataset.…”
Section: Introductionmentioning
confidence: 99%
“…4 Hangzhou Women's Hospital (Hangzhou Maternity and Child Health Care Hospital), Hangzhou, China. 5 Department of Dermatology, Hangzhou Hospital of Traditional Chinese Medicine, Zhejiang 310007, Hangzhou, China. 6 WBBC Shandong Center, Binzhou Medical University, Yantai, Shandong, China.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Osteoporosis could be clinically diagnosed by measuring the bone mineral density (BMD), which is a highly heritable trait [ 2 ]. Some modifiable environmental factors such as body weight [ 3 ], physical activity [ 4 ], sleep behavior [ 5 ], and inflammatory disease [ 6 ] could have an impact on bone mass gain and the development of osteoporosis. Other non-modifiable factors included sex, age, and genetic factors.…”
Section: Introductionmentioning
confidence: 99%